2023
DOI: 10.7759/cureus.35919
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Clinical Profiles of Patients With Cerebrovascular Accident (Stroke) in a Tertiary Care Hospital in Jharkhand

Abstract: Introduction Stroke is a devastating and disabling cerebrovascular disease with a significant amount of residual deficit. The prevalence of stroke is in a rising trend in India. Larger studies are needed for the evaluation of risk factors. Material and methods This cross-sectional study aimed to assess the clinical profile of patients with stroke. The demographic details of the patients were taken, comorbidities were noted, and laboratory tests were done. Observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In oncology, ADRs significantly impact patient outcomes [23][24][25]. Studies on voluntarily reported ADRs involving anticancer drugs highlight the prevalence among 41-60year-olds, particularly female subjects, with skin issues and shivering as common symptoms associated with taxanes, targeted therapies, and platinum drugs [23]. Most of the ADRs were mild and preventable [23].…”
Section: Number Of Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…In oncology, ADRs significantly impact patient outcomes [23][24][25]. Studies on voluntarily reported ADRs involving anticancer drugs highlight the prevalence among 41-60year-olds, particularly female subjects, with skin issues and shivering as common symptoms associated with taxanes, targeted therapies, and platinum drugs [23]. Most of the ADRs were mild and preventable [23].…”
Section: Number Of Responsesmentioning
confidence: 99%
“…Studies on voluntarily reported ADRs involving anticancer drugs highlight the prevalence among 41-60year-olds, particularly female subjects, with skin issues and shivering as common symptoms associated with taxanes, targeted therapies, and platinum drugs [23]. Most of the ADRs were mild and preventable [23]. Another study reported that infections, nausea, and febrile neutropenia were frequent, involving drugs like platinum compounds and taxanes, with about 30.8% of reactions being preventable [24].…”
Section: Number Of Responsesmentioning
confidence: 99%
“…19 According toMohammedin et al (2021), the age group most affected by stroke is the non-elderly group, aged 50-59 years (49%).…”
mentioning
confidence: 99%